Survei Sikap Sosial Siswa Melalui Pembelajaran Penjasorkes di SMAN 1 Ngawen Kabupaten Blora Tahun 2021 - Vittary Awanda Puspitaningrum; Hermawan Pamot Raharjo (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the level of success of physical education and physical education learning on the social attitudes of class X students of SMAN 1 Ngawen in Blora Regency during the current covid-19 period. This study uses a quantitative method through a survey with a descriptive approach. The research sample was 128 students. The sampling technique is proportional stratified random sampling. Methods of data collection using observation, documentation, and questionnaires. Data analysis with descriptive analysis of percentages. The results of this study are according to report cards on the attitude aspect of 19.86% (28 students) categorized as very good, while 80.14% (113 students) in the good category. The conclusion of this study, that most of the class X students at SMAN 1 Ngawen have been able to apply several aspects of social life through online learning according to the homeroom's assessment of attitudes including discipline, cooperation, honesty, mutual respect, responsibility, self-confidence, and tolerance contained in aspects of attitude assessment through observation, self-assessment, assessment between students, and journals with good categories.